Cold Stress in Wheat: Plant Acclimation Responses and Management Strategies - Hassan, Muhammad A.; Xiang, Chen; Farooq, Muhammad; Muhammad, Noor; Yan, Zhang; Hui, Xu; Yuanyuan, Ke; Bruno, Attiogbe K.; Lele, Zhang; Jincai, Li (Frontiers in Plant Science, 2021)
Unpredicted variability in temperature is associated with frequent extreme low-temperature events. Wheat is a leading crop in fulfilling the global food requirements. Climate-driven temperature extremes influence the vegetative and reproductive growth of wheat, followed by a decrease in yield. This review describes how low temperature induces a series of modifications in the morpho-physiological, biochemical, and molecular makeup of wheat and how it is perceived. To cope with these modifications, crop plants turn on their cold-tolerance mechanisms, characterized by accumulating soluble carbohydrates, signalling molecules, and cold tolerance gene expressions. This review also discusses the integrated management approaches to enhance the performance of wheat plant against cold stress. Here we propose strategies for improving the adaptive capacity of wheat besides alleviating risks of cold anticipated with climate change.